Thieme anatomy posters bones and muscles - Michael Schuenke; Erik Schulte; Udo Schumacher (Thieme Medical Publishers, 2014)
Thieme Anatomy Posters help students quickly and easily identify all the important bones and muscles in the human body. Each life-sized (22 x 62 inches) and clearly labeled poster features bones on one side and muscles on the other. These handy anatomy reference tools can be used by professors and students in dissection labs as well as by physical therapists and osteopaths in their daily practice.